Environmental & architectural phenomenology. Vol. 5, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 1994)
Vol. 5, No. 1, Winter 1994 (includes “items of interest,” "citations received,” book reviews of Jerri Holan's Norwegian Wood & Alexander Wilson's The Culture of Nature, and essays by Murray Silverstein & Jeffrey Ediger).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals